2020
DOI: 10.3389/fpsyg.2020.02039
|View full text |Cite
|
Sign up to set email alerts
|

Response to a Specific and Digitally Supported Training at Home for Students With Mathematical Difficulties

Abstract: The present study evaluated the effectiveness of a shortened, specialized, and digitally supported training program for enhancing numerical skills in primary and secondary school children with mathematical difficulty (MD). The participants ( n = 57) were randomly assigned to two groups: for the experimental group, the tasks were differentiated and adapted to each student’s learning profile. Moreover, children of this group used a Web App (i.e., “I bambini contano” or “Children count” in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…These results can provide new information for the formulation of interventions for adults with DD. Many efforts have been made in the last decades to support students with mathematical learning difficulties [46,47], but attempts to propose age-appropriate trainings for adults with numerical difficulties are rare [48,49]. Our study highlights the need to design innovative interventions that may target deficiencies in the cognitive, numerical, social, and emotional dimensions of adults with DD.…”
Section: Discussionmentioning
confidence: 90%
“…These results can provide new information for the formulation of interventions for adults with DD. Many efforts have been made in the last decades to support students with mathematical learning difficulties [46,47], but attempts to propose age-appropriate trainings for adults with numerical difficulties are rare [48,49]. Our study highlights the need to design innovative interventions that may target deficiencies in the cognitive, numerical, social, and emotional dimensions of adults with DD.…”
Section: Discussionmentioning
confidence: 90%
“…The selection criteria excluded the totally “clinic-based” rehabilitative programs. Still, a sub-group of papers (7/98–7%) ( 28 , 40 , 44 , 61 , 85 , 93 , 114 ) describing hybrid interventions (i.e., partially administered via telerehabilitation and during “in clinic” sessions) was included in the review. The remaining papers (91/98–93%) were identified as entirely administered via telerehabilitation; a sub-classification was applied to the latter group to differentiate the home-based (82/98) from the school-based programs (9/98) ( 27 , 62 , 63 , 80 , 103–106 , 120 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several authors suggest different teaching methodologies from individual, differentiated and contextualized approach (Oliva, 2023;Bal, 2023;Ahdhianto et al, 2020;Prast et al, 2018;Ngunjiri, 2022;Hidayati, 2020;Root et al, 2020;Fabian et al, 2018;Cannon, 2017;Lawson, 2018;Re et al, 2020;Dinglasan et al, 2023;Saguin et al, 2020;Strogilos et al, 2023;Bobis et al, 2021;Jackaria et al, 2019;Picat & Natividad, 2023;Aguhayon et al, 2023;Hackenberg et al, 2021) to group and collaborative (Hofmann & Mercer, 2016;Pons et al, 2014;Algani, 2021;Schwarz et al, 2021;Haftamu, 2017;Rico-Bautista et al, 2019;Sofroniou & Poutos, 2016;Golden, 2020;) and cooperative learning (Cortez et al, 2023;Entonado & García, 2003;Suryatin, 2020;Ningsih, 2019;Catarino et al, 2019;Jones, 2018;Furner, 2022;Chan & Idris, 2017;Klang et al, 2021;Kwame & Samuel, 2020;Anderson, 2003). These studies showed more positive outcomes using cooperative learning methodologies due to the shared tasks among students.…”
Section: Introductionmentioning
confidence: 99%